Possession : a romance - Byatt, A. S. (Antonia Susan), 1936- (Vintage, 2018)
Winner of the 1990 Booker Prize, this novel describes the romance between two 19th century poets and the parallel relationship of their two biographers and includes passages of 'Victorian verse'.